DEVELOPMENT OF THE EDUCATIONAL PROGRAMMES FOR PHYSICAL EDUCATION AND SPORTS - Marina Yu. Shchennikova; Marina A. Borisevich (Высшее образование в России, 2016)
The paper focuses on the analysis of educational programmes in the sphere of physical training and sport implemented at Lesgaft University The authors present the enrolment data and show the University role in training personnel for the region needs. Special attention is paid to the system of advanced education and personnel retraining in the sphere of physical education, sport and health.